Tequila : A Natural and Cultural History - Valenzuela Zapata, Ana Guadalupe, 1963- (Book collections on Project MUSE., 2004)
"In Tequila! A Natural and Cultural History, Ana G. Valenzuela-Zapata, leading agronomist in Mexico's tequila industry, and Gary Paul Nabhan, one of America's most respected ethnobotanists, plumb the myth of tequila as they introduce the natural history, economics, and cultural significance of the plants cultivated for its production."--Jacket.